Black market organ transplantation and bioethics - Miloshevska, Tanja (Филозофски факултет – Скопје, Центар за интегративна биоетика при Филозофскиот факултет во Скопје., 2018)
Nowadays, a new bioethics vocabulary for organ transplantation has appeared, nurtured by severe organ deficiencies and characterized by controversy generated through asystolic protocols, donation by living persons and, most recently, the problematic issue of applying market forces to organ donation. This article highlights illustrations of human exploitation include the obtaining of organs from live donors and unethical forms of medical research. Ultimately, discrimination and exploitation are similar, despite the varying contexts of bioethics, because they both entail the instrumentalization of human beings. This paper looks precisely at black market organ transfer which is the consequence of a gross imbalance between supply and demand. Another issue challenging the ethical boundaries of voluntary donation was the commercialization of donation or selling organs. Considerations of this commercialization of organ trafficking has led to questions of who truly benefits from this practice? Clearly, the organ recipient benefits, as do the brokers, hospitals, and doctors who participate. Does the donor generally benefit from this practice? Who ends up making the money? Who carries the greatest risk and burden? To some extent market force in the area of organ donation-regardless of how negligible- will quickly fail into “black market” commodities trading. The cruelty of organ donation has been the rule and not the exception in many countries where money is offered in exchange for transplantable organs.
Keywords: bioethics, black market, organ transplatation, human exploitation